Advancing freeze drying as an innovative technique for preserving Kashmiri saffron (Crocus sativus L.) - Shubli Bashir; Syed Zameer Hussain; Nusrat Jan; Bazila Naseer; Tanweer Alam (Scientific Reports)
Abstract This study evaluated the effect of different freeze-drying (FD) temperatures (-50 °C, -60 °C, -70 °C, and − 80 °C) on quality parameters of saffron stigmas. The physicochemical properties (moisture, ash content, and water activity), color profile, thermal stability, antioxidant capacity, total phenolic content, bioactive components (crocin, picrocrocin, and safranal), microstructure, and structural characteristics were analyzed. Moisture content (11.10-11.19%), water activity (0.533–0.542), and ash content (4.708–4.712%) showed non-significant differences across temperature, significant variations were observed in color parameters and antioxidant properties. FD at -80 °C for 44 h demonstrated superior preservation of color attributes (a*=40.09, b*=17.43), antioxidant capacity (69.63%), and total phenolic content (72.41 mg GAE/g). Although the effect on bioactive components was non-significant, -80 °C treatment showed optimal retention of crocin (90.14 mg/g), picrocrocin (9.48 mg/g), and safranal (1.80 mg/g). Differential scanning calorimetry (DSC) analysis revealed distinct stability patterns with − 80 °C dried samples exhibited the highest thermal stability. Scanning electron microscopy (SEM) revealed better structural preservation and less shrinkage at -80 °C, while Fourier-transform infrared spectroscopy (FTIR) confirmed molecular stability of bioactive compounds across all treatments. These findings suggest that FD at -80 °C for 44 h is optimal for preserving the quality attributes and bioactive components of saffron, offer a promising approach for producing shelf-stable and high quality saffron.